2019
DOI: 10.11648/j.abb.20190704.13
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization of Two Wild Varieties of Edible Orchid Tubers

Abstract: The physical properties of agricultural products are necessary for the design of equipment for post-harvest treatments and storage. The physical characteristics of two varieties (Ateehteu and Lamsie) of wild orchid tubers used for the production of an endogenously processed food eaten as a meat replacement were determined. Directly measured properties (tuber length, width, thickness, mass, true volume and bulk volume) and derived properties (sphericity, shape index, size, porosity, true and bulk density) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Nyam Ngub as named by most fufu corn eaters or chengni from the Ngemba's , achu eaters of the North West region of Cameroon is an endogenously processed food from terrestrial wild orchid tubers and consumed in the form of meat snack, relish, meat substitute and/ or meat replacement [30,31]. To produce Nyam ngub, the wild orchid tubers are washed, drained, crushed in a mortar after which water is added and mixed.…”
Section: Nyam Ngubmentioning
confidence: 99%
See 2 more Smart Citations
“…Nyam Ngub as named by most fufu corn eaters or chengni from the Ngemba's , achu eaters of the North West region of Cameroon is an endogenously processed food from terrestrial wild orchid tubers and consumed in the form of meat snack, relish, meat substitute and/ or meat replacement [30,31]. To produce Nyam ngub, the wild orchid tubers are washed, drained, crushed in a mortar after which water is added and mixed.…”
Section: Nyam Ngubmentioning
confidence: 99%
“…Wood ash extract made from special woods and/ or plant stems is then added and homogenized after which the mix is packaged in flamed plantain leaves and steam cooked for about 40-60 mins. The gel-like cooked product is cooled and eaten directly or a the source eaten along with corn fufu, or other cereal related meals [30].…”
Section: Nyam Ngubmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that Dendrobium spp., Gastrodium spp., and the hyacinth orchid (Bletilla striata) have been used in the treatment of ailments like hemorrhages of the stomach or lungs, uterine bleeding, and nose bleeds, as well as whooping cough [1,33], and more medicinal uses are being uncovered across the world [11,60].…”
Section: Edible Orchids Of Cameroonmentioning
confidence: 99%
“…Orchids belong to a very diverse, attractive and economically important family Orchidaceae, distributed from tropical to temperate zones, with nearly 30,000 known wild species and about 100,000 hybrids [1]. All orchids are herbaceous plants in life forms and classified into four categories in natural habitat: Orchids are popularly known for their beautiful flowers which make them a plant resource of great exotic, economic importance in the global horticultural industry.…”
Section: Introductionmentioning
confidence: 99%